NIR upconversion fluorescence glucose sensing and glucose-responsive insulin release of carbon dot-immobilized hybrid microgels at physiological pH. Issue 2 (12th December 2016) - Wang, Hui; Yi, Jinhui; Yu, Yanyan; Zhou, Shuiqin
Abstract : The NIR upconversion fluorescence glucose sensing and glucose-responsive insulin release of carbon dot-immobilized hybrid microgels at physiological pH is reported. Abstract : This work reports the preparation of multifunctional hybrid microgels based on the one-pot free radical dispersion polymerization of hydrogen-bonding complexes in water, formed from hydroxyl/carboxyl bearing carbon dots with 4-vinylphenylboronic acid and acrylamide comonomers, which can realize the simultaneous optical detection of glucose using near infrared light and glucose-responsive insulin delivery.